The 2018–2019 weak El Niño: Predicting the risk of a dengue outbreak in Machala, Ecuador. (16th August 2020) - Petrova, Desislava; Rodó, Xavier; Sippy, Rachel; Ballester, Joan; Mejía, Raul; Beltrán‐Ayala, Efraín; Borbor‐Cordova, Mercy J.; Vallejo, G. Mauricio; Olmedo, Alfredo J.; Stewart‐Ibarra, Anna M.; Lowe, Rachel
Abstract: Between October 2018 ‐ May 2019, sea surface temperature conditions in the central‐eastern tropical Pacific indicated a mild El Niño event. In May 2019, the global El Niño Southern Oscillation (ENSO) forecast consensus was that these generally weak warm patterns will persist at least until the end of the northern hemisphere summer. El Niño and its impact on local climatic conditions in southern coastal Ecuador influence the inter‐annual transmission of dengue fever in the region. In this study, we use an ENSO model to issue forecasts of El Niño for the year 2019, which are then used to predict local climate variables, precipitation and minimum temperature, in the city of Machala, Ecuador. All these forecasts are incorporated in a dengue transmission model, specifically developed and tested for this area, to produce out‐of‐sample predictions of dengue risk. Predictions are issued at the beginning of January 2019 for the whole year, thus providing the longest forecast lead time of 12 months. Preliminary results indicate that the mild and ongoing El Niño event did not provide the optimum climate conditions for dengue transmission, with the model predicting a very low probability of a dengue outbreak during the typical peak season in Machala in 2019. This is contrary to 2016, when a large El Niño event resulted in excess rainfall and warmer temperatures in the region, and a dengue outbreak occurred 3 months earlier than expected. This event was successfully predicted using a similar prediction framework to the one applied here. With the present study, we continue our efforts to build and test a climate service tool to issue early warnings of dengue outbreaks in the region. Abstract : We use an ENSO model to forecast El Niño in 2019. We also predict precipitation and minimum temperature in the city of Machala, Ecuador. These forecasts are incorporated in a dengue model for Machala. Predictions are issued in January 2019 for the whole year. Results indicate the mild El Niño event predicted to continue until the end of 2019 did not provide optimum conditions for dengue transmission, with low probability of a dengue outbreak during the peak season in Machala. (a) Forecast of the sea surface anomalies in the Niño3.4 region for the months January 2019 to January 2020 (beige curve). (b) Predicted median (dashed purple curve) and 95% prediction interval (purple shaded area) for log dengue incidence rates (cases per 100, 000 population) in Machala, Ecuador for the months January to December 2019. The five‐year mean dengue incidence (blue curve) and upper 95% confidence interval (red curve) for the period 2014–2018 is shown. The available observations are provided in a dashed black curve.